Treatment-related alteration of cortisol predicts change in neuropsychological function during acute treatment of late-life anxiety disorder - Lenze, Eric J. (Int J Geriatr Psychiatry, 2011)
OBJECTIVE: Older adults with anxiety disorders are burdened by impairment in neurocognition, which may be mediated by elevated circulating cortisol levels. In a randomized controlled trial of acute serotonin-reuptake inhibitor treatment for late-life anxiety disorder, we examined whether change in salivary cortisol concentrations during treatment predicted improvements in measures of memory and executive function. METHODS: We examined 60 adults aged 60 and older, who took part in a 12-week trial of escitalopram vs. placebo for Generalized Anxiety Disorder. All subjects had pre- and post-treatment assessments that included monitoring of peak and total daily cortisol and a comprehensive neuropsychological evaluation. RESULTS: Salivary cortisol changes during treatment showed significant associations with changes in immediate and delayed memory, but no association with executive tasks (measures of working memory and set-shifting). Analyses suggested that a decrease in cortisol due to serotonin-reuptake inhibitor treatment was responsible for the memory changes: memory improvement was seen with cortisol reduction among patients receiving escitalopram, but not among patients receiving placebo. CONCLUSION: Serotonin-reuptake inhibitor-induced alteration in circulating cortisol during treatment of Generalized Anxiety Disorder predicted changes in immediate and delayed memory. This finding suggests a novel treatment strategy in late-life anxiety disorders: targeting HPA axis dysfunction to improve memory.